Reorganização de redações no Brasil: análise dos processos de produção do Estadão e HuffPost - Silva, Jonas Gonçalves da (2018)
The journalistic work space was deeply modified by structural changes in the last decades. This process was, partially, identified by researchers as Ramón Salaverría, who developed the concept of “journalistic convergence” to define the reasons that made traditional media companies search for a conformation that could optimize their workflows, considering as a priority the digital platform, in spite of the existence in some business groups of legacy media platforms, like the newspaper or the radio. In parallel, the journalism market diversification, with the launch of new business models, created a demand for an increase of this research line, including the “digital natives”, enterprises that, although being direct derivatives from the internet expansion, also had to, in some cases, make organizational readjustments. This research work analyses, beyond a comparative study, the changes in the newsrooms and in the productive processes of two news sites, occurred from 2014 to 2017: Estadão.com.br, from the newspaper O Estado de S. Paulo, characterized in this work as a Digital Analogic Newsroom (DAN) due to its hybrid condition; and HuffPost Brazil, the Digital Native Newsroom (DNN), that represents in the country the HuffPost (USA), being a branch created in partnership with Abril Group and currently managed by Oath (the result of a fusion between the technology companies AOL and Yahoo!, both acquired by Verizon). In this way, this dissertation aims to present indicators that allow verify how different business models arranged three key issues to guide their reconfiguration processes: 1) inherent specificities from the respective business models; 2) management guidelines; and 3) necessity of changes in the productive processes, motivated by the technological evolution. The research methods used were the following: bibliographic review of the theoretical concepts of “convergence”, “media ecosystem” and “integrated journalism”; presential and systematized observations of the newsrooms work routines phases; and case studies. In the visits made, were observed schedule, investigation, edition and news publication procedures, featuring the use of digital technologies, including social media platforms and audience monitoring tools.